Melek Literasi Keuangan Dalam Meningkatkan Kesejahteraan Ekonomi Individu Dan Masyarakat Studi Kasus Masyarakat Desa Jambur Padang Matinggi - Eva Suryani; Novebri Novebri (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The aim of this research is to determine the role of financial literacy in improving the economic well-being of individuals and the community as a whole, with a specific emphasis on the residents of Jambur Padang Matinggi. The ability to understand and use various financial skills, such as budgeting, investing, and personal financial management, is referred to as financial literacy. This study emphasizes the relationship between better economic stability and higher financial literacy among community members. According to information gathered through surveys and interviews, individuals with greater financial knowledge are more capable of making sound financial decisions, which in turn leads to increased savings and investments in local businesses. Furthermore, the results indicate that financial literacy programs can have a significant impact on overall community growth by encouraging saving habits and borrowing money wisely. The study underscores the importance of integrating financial literacy programs into community development strategies, especially in rural areas where financial education resources are limited. Therefore, enhancing financial knowledge emerges as a crucial component in improving the prosperity of both individuals and communities.